1997
DOI: 10.1111/j.1399-0039.1997.tb02753.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of TAP1 and TAP2 in Japanese patients with rheumatoid arthritis

Abstract: Contribution of polymorphism of transporter associated with antigen processing 1 and 2 (TAP1 and 2) alleles to pathogenesis of Japanese rheumatoid arthritis (RA) was studied in 92 RA patients by PCR-RFLP. The allele frequency of TAP2A was slightly low (38.0%) and the frequencies of TAP2B and TAP2C were slightly high (39.7% and 17.9%) in RA, but these differences were not significant. These increases and decrease were due to the positive or negative associations with HLA-DRB1*0405. It was very likely that sligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The LD block to which HLA–DQB2 belongs also contains the TAP1/TAP2 genes, which function in the delivery of peptides to the endoplasmic reticulum for the assembly of class I MHC molecules and the HLA–DMA/DMB genes, which play a central role in the peptide loading of class II MHC molecules. The association of polymorphism in these genes with RA has been investigated in several studies, and no statistically significant association has been observed (37–39). In our study, several SNPs in the TAP2 and HLA–DMB genes were genotyped, but no significant associations were observed in the DRB1‐conditioned analysis (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The LD block to which HLA–DQB2 belongs also contains the TAP1/TAP2 genes, which function in the delivery of peptides to the endoplasmic reticulum for the assembly of class I MHC molecules and the HLA–DMA/DMB genes, which play a central role in the peptide loading of class II MHC molecules. The association of polymorphism in these genes with RA has been investigated in several studies, and no statistically significant association has been observed (37–39). In our study, several SNPs in the TAP2 and HLA–DMB genes were genotyped, but no significant associations were observed in the DRB1‐conditioned analysis (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The association of TAP1 and TAP2 gene polymorphisms with RA has been studied in various countries, with conflicting results (Wordsworth et al ., 1993; Marsal et al ., 1994; Singal & Qiu, 1994; Vandevyver et al ., 1995; Hillarby et al ., 1996; Takeuchi et al ., 1997; Tuokko et al ., 1998; Vinasco et al ., 1998; Vejbaesya et al ., 2000). However, all known TAP1 and TAP2 polymorphisms were not systematically investigated in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Genes encoding the two TAP subunits, TAP1 and TAP2 are located within the MHC class II region between the DPB1 and DQB1 loci [5,6], and variations in rat TAP genes have been reported to be associated with differences in the spectrum of MHC class I‐binding peptides [7]. Many diseases associated with HLA have been investigated for the influence of TAP [8–13]. Two dimorphic sites within TAP1, Ile/Val‐333 and Asp/Gly‐637, and four dimorphic sites within TAP2, Val/Ile‐379, Ala/Thr‐565, Thr/Ala‐665 and Stop/Gln‐687, have been widely investigated [9].…”
Section: Introductionmentioning
confidence: 99%